Extraocular Muscle Volumetry for Assessment of Thyroid Eye Disease. Issue 1 (March 2022) - Bontzos, Georgios; Papadaki, Efrosini; Mazonakis, Michael; Maris, Thomas G.; Tsakalis, Nikolaos G.; Drakonaki, Eleni E.; Detorakis, Efstathios T.
Abstract : Background: In this study we evaluate the diagnostic accuracy of extraocular muscle volumetry in detecting thyroid eye disease and to compare the results with simple measurements of maximal medial rectus (MR) diameter. Methods: Cross-sectional study that included 47 eyes of 47 patients with thyroid eye disease and 47 healthy controls. Patients underwent slitlamp examination and imaging consisting of computed tomography scans. Image segmentation and volume measurements were performed by 2 independent researchers. Intraobserver and interobserver reliability testing was also conducted. Results: Total extraocular muscle volume was 7.31 ± 1.88 cm 3 and medial volume was 2.38 ± 0.73 cm 3 in the study group. In this group, the maximum measured diameter of the MR was 6.67 ± 0.35 mm. MR volume was statistically associated with maximum MR diameter (r = 9.78; P < 0.001). Both MR volume and maximum MR diameter measurements showed good predictive efficacy as shown using receiver operator characteristic curve analysis. Conclusions: Complications of thyroid eye disease are often sight threatening, and timely diagnosis is crucial for the management of the entity and its sequelae. The results of this study imply that simple measurements of maximum MR diameter are sensitive enough to establish diagnosis.